Stability of okra hybrids and cultivars - Paiva, Waldelice Oliveira de; Costa, Cyro Paulino da (Pesquisa Agropecuaria Brasileira, 1994)
Yields stability of eleven cultivars and twenty hybrids of okra (Abelmoschus esculentus (L.) Moench) were studied at two seasons (Winter and Summer) during two years, in Piracicaba, SP, Brazil. Santa Cruz-47 cultivar and A x C, E x A and F x A hybrids showed large stability, measured by stability parameters (b), S2d and R2. The A x-F hybrid was the best, but it showed significant deviations. In general, okra genotypes showed sensibility to the environment changes and the hybrids were the most stable and with frequencies three times superior to those of the cultivars.